2020
DOI: 10.1039/d0cp02674c
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry breaking of the bending mode of CO2 in the presence of Ar

Abstract: The weak infrared spectrum of CO2-Ar corresponding to the (0111) <-- (0110) hot band of CO2 is detected in the region of the carbon dioxide ν3 fundamental vibration (~2340 cm-1),...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…We have previously reported spectra in the region of the CO 2 (v 1 , v 2 l2 , v 3 ) = (01 1 1) ! (01 1 0) hot band near 2337 cm À 1 for CO 2 -Ar, [8] À Ne, [9] À Xe, [5] À N 2 [10] and À CO. [11] Transitions from this excited state (01 1 0) to the combination state (01 1 1) exhibit b-type selection rules, like the ν 3 fundamental. The (01 1 0) lower state bends have A 1 (i-p) and B 1 (o-p) symmetry with allowed even or odd K a levels respectively.…”
Section: Chemistryselectmentioning
confidence: 94%
“…We have previously reported spectra in the region of the CO 2 (v 1 , v 2 l2 , v 3 ) = (01 1 1) ! (01 1 0) hot band near 2337 cm À 1 for CO 2 -Ar, [8] À Ne, [9] À Xe, [5] À N 2 [10] and À CO. [11] Transitions from this excited state (01 1 0) to the combination state (01 1 1) exhibit b-type selection rules, like the ν 3 fundamental. The (01 1 0) lower state bends have A 1 (i-p) and B 1 (o-p) symmetry with allowed even or odd K a levels respectively.…”
Section: Chemistryselectmentioning
confidence: 94%
“…While we reproduced this splitting in argon matrixes, in neon matrixes we observe only a splitting for the CO 2 ν 2 (E 1u ) transition . It has been shown that the matrix environment makes the two degenerate bending vibrations distinguishable, leading to the observed splitting of the band that corresponds to the bending vibration. …”
Section: Resultsmentioning
confidence: 49%
“… 11 It has been shown that the matrix environment makes the two degenerate bending vibrations distinguishable, leading to the observed splitting of the band that corresponds to the bending vibration. 37 39 …”
Section: Resultsmentioning
confidence: 99%
“…A T-shaped structure was established, with the Ar atom located to the “side” of the CO 2 molecule, adjacent to the C atom at an intermolecular separation of about 3.5 Å. Since then, there have been many more microwave , and infrared studies. The trimer CO 2 -Ar 2 has also been detected in the microwave and infrared regions.…”
mentioning
confidence: 99%
“…Our spectra were recorded as described previously, , using a pulsed supersonic slit jet expansion probed by a rapid-scan optical parametric oscillator source. The slit width was set at 12.5 μm, narrower than we have previously used in order to encourage the formation of larger clusters.…”
mentioning
confidence: 99%